719 CD122-directed interleukin-2 complexes and αPD-L1 differentially require innate and adaptive immunity to treat local and metastatic bladder cancer. (10th December 2020) - Reyes, Ryan; Deng, Yilun; Zhang, Deyi; Ji, Niannian; Mukherjee, Neelam; Wheeler, Karen; Gupta, Harshita; Kancharla, Aravind; Garcia, Myrna; Kornepati, Anand; Svatek, Robert; Curiel, Tyler
Abstract : Background: αPD-L1 bladder cancer (BC) immunotherapy is effective in <30% of cases. 1 To address the large αPD-L1-unresponsive subset of patients, we tested αIL-2/IL-2 complexes (IL-2c) that block IL-2 from binding high-affinity IL-2Rα (CD25) for preferential IL-2Rβ (CD122) binding. 2 Immunosuppressive regulatory T cells capture IL-2 by CD25 whereas antitumor CD8+ T, γδ T, and NK cells use CD122. We hypothesized that the tumor microenvironment, including local immune cells in primary versus metastatic BC, differentially affects immunotherapy responses and that IL-2c effects could differ from, and thus complement αPD-L1. Methods: We used PD-L1+ mouse BC cell lines MB49 and MBT-2, for orthotopic, intravesical (i.e., in bladder) and intravenous challenge studies of local versus lung metastatic BC. Results: αPD-L1 or IL-2c alone reduced tumor burden and extended survival in local MB49 and MBT-2. Using in vivo cell depletions, we found that γδ T cells and NK cells, but strikingly not CD8+ T cells, were necessary for IL-2c efficacy in bladder. We confirmed γδ T cell requirements for IL-2c, but not αPD-L1 efficacy in γδ T cell-null TCRδKO mice. TCRβKO conventional T cell-null mice exhibited IL-2c, but not αPD-L1 responsiveness for orthotopic BC treatment. Neither agent alone treated lung metastatic MB49 or MBT-2 but the drug combination improved survival in both tumor models. Combination treatment effects in lungs were distinct from bladder, requiring CD8+ T and NK cells, but not γδ T cells. Conclusions: BC immunotherapy effects differ by anatomic compartment and use distinct mechanisms to treat primary and metastatic BC. CD122-directed IL-2 is a promising BC immunotherapy strategy, and IL-2c is a candidate mediator through innate immune effects. αPD-L1 could improve IL-2c efficacy by engagement of adaptive immune responses including to improve metastatic disease treatment efficacy. Ethics Approval: All procedures involving animals in this study were approved by the UT Health San Antonio Institutional Animal Care and Use Committee (IACUC) and conducted in accordance with UT Health San Antonio Department of Laboratory Animal Resources standards. References: Shah AY, Gao J, Siefker-Radtke AO. Five new therapies or just one new treatment? A critical look at immune checkpoint inhibition in urothelial cancer: Future Medicine, 2017. Arenas-Ramirez N, Zou C, Popp S, et al. Improved cancer immunotherapy by a CD25-mimobody conferring selectivity to human interleukin-2. Science translational medicine 2016;8(367):367ra166-367ra166.